Temperature-induced shape morphing of bi-metallic structures. (1st May 2020) - Taniker, S.; Celli, P.; Pasini, D.; Hofmann, D.C.; Daraio, C.
Highlights: Thermally-morphing structures are generated via displacement-amplifying mechanisms. The mechanism leverages thermal expansion mismatches between different metals. Numerical results are compared to experiments on Ti-Al water-jet-cut samples. A mechanistic model is developed to quantify the influence of the design parameters. The design is analyzed for lunar temperatures, highlighting a potential application. Abstract: In this work, we study the thermo-mechanical behavior of metallic structures designed to significantly change shape in response to thermal stimuli. This behavior is achieved by arranging two metals with different coefficient of thermal expansion (CTE), Aluminum and Titanium, as to create displacement-amplifying units that can expand uniaxially. In particular, our design comprises a low-CTE bar surrounded by a high-CTE frame that features flexure hinges and thicker links. When the temperature increases, the longitudinal expansion of the high-CTE portion is geometrically constrained by the low-CTE bar, resulting in a large tangential displacement. Our design is guided by theoretical models and numerical simulations. We validate our approach by fabricating and characterizing individual units, one dimensional arrays and three-dimensional structures. Our work shows that structurally robust metallic structures can be designed for large shape changes. The results also demonstrate how harsh environmental conditions (e.g., the extreme temperature swings that are characteristic of extraterrestrial environments) can be leveraged to produce function in a fully passive way.